Performance analysis and improvement of digital communications in Nakagami-m fading channels - Ma, Xinyan (Nanyang Technological University, 2021)
Nakagami-m fading model is summed up by Nakagami from a large number of experimental data in 1960. It is a very flexible model with the fading parameter m and has a relatively simple form mathematically. In this Thesis, we did the analysis and simulation to evaluate the bit error rate (BER) performance for Nakagami-m fading channels. After the performance analysis, the problem comes to optimization. To make compensation for the loss caused by the fading effect, we here choose to apply some combining schemes at the receive side. Since the maximal ratio combining (MRC) scheme yields an optimal performance for coherent modulations, it is analyzed and simulated. From the simulation results, we can see that the MRC scheme can help to improve the system performance, and its ability increases with the number of antennas at the receiver side. Through our analysis, we found that the existing works have not taken the constraint of the total transmitted energy into consideration. So, we also made a supplement analysis on that case. The curves of the corresponding theoretical results are also plotted and found consistent with the simulation results. The selection combining (SC) scheme is also analyzed due to its simplicity, and a comparison between the two schemes is made. Furthermore, since the MRC scheme requires full knowledge of all channel parameters, which leads to high complexity for the receivers, we tried to find a balance between system performance and complexity by introducing the hybrid combining scheme. The simulation result for the hybrid selection/maximal-ratio combining (HS/MRC) scheme is consistent with our analysis.